The Effect of the Mixture of Plastic Waste as a Lightweight Concrete Material - Nurmaidah Nurmaidah; Yudhis Tira Pradana (Budapest International Research and Critics University, 2019)
Concrete has many functions, and is also an important role in maintaining building stability and strength. By using plastic fiber as a lightweight concrete mixture material, it is expected to increase the compressive strength of the lightweight concrete, and also to reduce the negative impact of waste plastic bottles. In this study also added differences in FAS for each specimen 0.5 and 0.6. With the difference in variation in each lightweight concrete specimen, it is expected to be able to know the performance of concrete from the different variations of PET and FAS. The use of PET and FAS mixtures in lightweight concrete produces the lightest Concrete at 9% PET mixture of fine aggregate weight. In full there are two results, FAS 0.5 = 11045 gr, and FAS 0.6 = 10981 gr. But for the maximum weight of test specimens it cannot be said to be structural lightweight concrete because it does not meet the minimum weight requirement of 1850 Kg / m3. The Slump test on the specimen shows that the highest Slump test is in FAS 0.6 with 9% PET mixture, with slump height reaching 135 mm or 13 cm, and 125 mm or 12.5 cm in FAS 0.5 9% PET mixture. Cylinder absorbance showed that the average maximum absorption of FAS specimens was 0.5 = 1,268% and FAS 0.6 = 1,212%. The value of the lightest concrete compressive strength is the most optimum in the variation of 3% PET specimens in FAS 0.5 and variation of 6% PET specimens in FAS 0.6. that is 25 Mpa and 19 Mpa. And for the SPSS test states that there is a significant difference in the differences in the variation of PET and FAS test objects.